Inhibition of IP3R/Ca2+ Dysregulation Protects Mice From Ventilator-Induced Lung Injury via Endoplasmic Reticulum and Mitochondrial Pathways - Ye, Liu; Zeng, Qi; Ling, Maoyao; Ma, Riliang; Chen, Haishao; Lin, Fei; Li, Zhao; Pan, Linghui (Frontiers in Immunology, 2021)
Rationale: Disruption of intracellular calcium (Ca2+) homeostasis is implicated in inflammatory responses. Here we investigated endoplasmic reticulum (ER) Ca2+ efflux through the Inositol 1,4,5-trisphosphate receptor (IP3R) as a potential mechanism of inflammatory pathophysiology in a ventilator-induced lung injury (VILI) mouse model. Methods: C57BL/6 mice were exposed to mechanical ventilation using high tidal volume (HTV). Mice were pretreated with the IP3R agonist carbachol, IP3R inhibitor 2-aminoethoxydiphenyl borate (2-APB) or the Ca2+ chelator BAPTA-AM. Lung tissues and bronchoalveolar lavage fluid (BALF) were collected to measure Ca2+ concentrations, inflammatory responses and mRNA/protein expression associated with ER stress, NLRP3 inflammasome activation and inflammation. Analyses were conducted in concert with cultured murine lung cell lines. Results: Lungs from mice subjected to HTV displayed upregulated IP3R expression in ER and mitochondrial-associated-membranes (MAMs), with enhanced formation of MAMs. Moreover, HTV disrupted Ca2+ homeostasis, with increased flux from the ER to the cytoplasm and mitochondria. Administration of carbachol aggravated HTV-induced lung injury and inflammation while pretreatment with 2-APB or BAPTA-AM largely prevented these effects. HTV activated the IRE1α and PERK arms of the ER stress signaling response and induced mitochondrial dysfunction-NLRP3 inflammasome activation in an IP3R-dependent manner. Similarly, disruption of IP3R/Ca2+ in MLE12 and RAW264.7 cells using carbachol lead to inflammatory responses, and stimulated ER stress and mitochondrial dysfunction. Conclusion: Increase in IP3R-mediated Ca2+ release is involved in the inflammatory pathophysiology of VILI via ER stress and mitochondrial dysfunction. Antagonizing IP3R/Ca2+ and/or maintaining Ca2+ homeostasis in lung tissue represents a prospective treatment approach for VILI.